2014
DOI: 10.2337/db14-1111
|View full text |Cite
|
Sign up to set email alerts
|

High Levels of Pigment Epithelium–Derived Factor in Diabetes Impair Wound Healing Through Suppression of Wnt Signaling

Abstract: Diabetic foot ulcer (DFU) caused by impaired wound healing is a common vascular complication of diabetes. The current study revealed that plasma levels of pigment epithelium-derived factor (PEDF) were elevated in type 2 diabetic patients with DFU and in db/db mice. To test whether elevated PEDF levels contribute to skin wound-healing delay in diabetes, endogenous PEDF was neutralized with an anti-PEDF antibody in db/db mice. Our results showed that neutralization of PEDF accelerated wound healing, increased an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
68
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 92 publications
(81 citation statements)
references
References 51 publications
(65 reference statements)
3
68
2
Order By: Relevance
“…A recent study found that circulating PEDF was higher in diabetic patients with foot ulcers (45). Neutralizing systemic PEDF via anti-PEDF antibody perfusion or in PEDF knockout mice improved healing rates coincident with higher wound angiogenesis, whereas systemic overexpression of PEDF slowed healing coincident with lower wound angiogenesis in diabetic mice.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…A recent study found that circulating PEDF was higher in diabetic patients with foot ulcers (45). Neutralizing systemic PEDF via anti-PEDF antibody perfusion or in PEDF knockout mice improved healing rates coincident with higher wound angiogenesis, whereas systemic overexpression of PEDF slowed healing coincident with lower wound angiogenesis in diabetic mice.…”
Section: Discussionmentioning
confidence: 97%
“…PEDF is expressed in many mammalian tissues (21,58) and exists at high levels in unwounded human dermis (23,38) and in the blood (42). While various tumors (58) and ischemic hearts (49) express relatively low levels of PEDF, a recent study showed that high systemic levels of PEDF may be etiologic for impaired healing in diabetics due to excessive antiangiogenesis (45). PEDF is produced by quiescent FBs (15,44) in normoxic conditions (49) and by keratinocytes (KCs) (14), and it is readily secreted into the ECM.…”
mentioning
confidence: 99%
“…The lifetime risk of a patient with diabetes developing a foot ulcer reaches as high as 25%, and it is believed that every 30 seconds a lower limb is lost somewhere in the world because of diabetes [2]. Angiogenesis plays an important role in skin maintenance and repair, depending on various kinds of cell participation and coordination, including endothelial precursor cells (EPCs) and endothelial cells (ECs) [3]. …”
Section: Introductionmentioning
confidence: 99%
“…PEDF modulates target cell responses by signaling via a family of unrelated high affinity receptors. The anti-angiogenic activity of PEDF is mediated by the laminin receptor (19)(20)(21); low-density lipoprotein receptor-related protein 6 (LPR6; Wnt co-receptor) (22); and cell surface F 1 F 0 -ATP synthase (23). The macrophage stimulating (16) and neurotrophic activities (24) of PEDF are mediated by adipose mice were more than >200 mg/dL by d 7, and remained at that level thereafter ( Figure 1A).…”
Section: Induction Of Diabetesmentioning
confidence: 98%